Behaviour of reinforced concrete beam under half-sine impulse load / Wan Nor Azdi Wan Ibrahim (Faculty of Civil Engineering, 1997)
Nowadays increasing use of high strength concrete (HSC) in construction industry has prompted the need to understand clearly its behaviour.One or the application of the high strength concrete beam (HSC) is the railway industry as the railway track sleepers. Therefore, this study will be concentrated on the behaviour of high strength concrete beam under half sine impulse load with respect to static loading and dynamic loading. Three numbers of high strength concrete (HSC) beam of size 125 mm x 150 mm x 1400 mm are casted with four nos. longitudinal reinforcement ( bottom 2T16 and top 2R6 ) together with R6 stirrup at 80 mm c/c spacing is mixed and cured as BS 1881. The concrete grade 60 N/mnr is used. One of the beam is tested under 4 point static load test until failure while the remaining two are tested under dynamic load test with minimum load of 50 % of yield load and maximum load of 60 % yield load. Half sine impulse load under 4 point test is applied for 3 millions and 5 millions with the frequency of 10 hertz. Due to the availability of testing machine, load control is used. Concrete strength of 60 N/mm2was achieve from the cube test to show that the concrete mix for high strength concrete is meet.The static test gaves the Young's modulus of 33.810 kN/mm2. In the dynamic test, rapid increase in deflection, crack mouth opening and crack length for the both beam cases. There is a loss in stiffness of the beam due to loss of gripping force between concrete and reinforcement. It seem that the response of the beam in term of deflection, crack mouth and crack length is not great during further application of load cycles.